Predicting organizational commitment via job satisfaction, gender, age, experience, and position: An empirical investigation in a private financial institution in Bahrain. - Eleswed, Muath (2014)
The purpose of this study was to investigate whether or not organizational commitment can be predicted by job satisfaction, gender, age, experience, and position in a private financial institution in Bahrain. One hundred and fifty-six subjects participated in this study. Using a stepwise multiple regression model, results revealed that job satisfaction was the only predictor of organizational commitment. Based on the results, implications and direction for further studies were made